Socialization and Assistance in the Utilization of Islamic Digital E-Book Applications as Learning Resources for Religious Counselors at KUA Telukjambe Timur Karawang (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The Islamic E-Book digital application which is the result of research in the form of the E-Maktabah digital application must be utilized as much as possible by the community, especially religious instructors who are tasked with teaching and providing Islamic insight lessons for their congregations in various taklim assemblies and mosques. Therefore, this Islamic E-Book digital application must be socialized to religious instructors as a source of learning and reference in increasing Islamic insight as well as assisting in effective and efficient ways of utilizing and using it. Socialization and assistance to religious instructors and the community regarding Islamic Digital Applications, namely E-Maktabah and providing education about studies in Islam is one way out to familiarize the community with continuing to learn through literacy activities that can be done anywhere without the need to create a crowd and suppress the spread of the Covid-19 virus. The activities carried out are as follows: Providing education about the importance of digital literacy and education about studies in Islam contained in the E-Maktabah application, making videos on how to use the E-Maktabah application to facilitate religious and community educators in read digital books wherever and whenever during this pandemic and conduct workshops and direct E-Maktabah assistance for religious instructors at KUA Telukjambe Timur Karawang. The results of the E-Maktabah socialization and mentoring